On the occasion of the fiftieth volume of the Scripta Medica (Banja Luka) - Stojiljković, Miloš P. (Scripta Medica, 2019)
The article was written by the current Editor-in-Chief of the scientific journal Scripta Medica (Banja Luka) on the occasion of publishing the final issue of the fiftieth volume of the journal. Founded in 1966, the Scripta Medica (Banja Luka) started as a local journal of the Banja Luka Medical Centre, its General Hospital, later belonging to the Association of Medical Doctors of the Bosnian Krajina region and the Republic of Srpska and the Faculty of Medicine, University of Banja Luka. Its eight editors were: Professor Andrija Mikeš (1966-1968), Dr Dragomir Todorović (1969-1971), Assistant Professor Zvonimir Klepac (1972-1974), Professor Branko Pikula (1975-1990), Professor Bogdan Žigić (1995-2009), Professor Rajko Igić (2010-2013), Professor Predrag Grubor (2014-2018) and Professor Miloš P. Stojiljković (since 6 August 2018). It used to appear twice a year or quarterly. The Scripta Medica (Banja Luka) has a peer-review process and tends to reach a status of well-established scientific journal.